Mental Health Challenges in the Saudi Legal Profession: (The Role of Case Specialization, Gender, and Experience) - Ridwan M. Alomri (مجلة العصر للعلوم الانسانية والاجتماع, 2025)
Legal professionals are subject to great psychological distress as they deal with long hours, complex case management, and emotionally charged disputes. Studies in Western countries have demonstrated these challenges. However, few data are available about the mental health of legal professionals in Saudi Arabia, which is different in cultural and professional aspects. Accordingly, this study illuminates the relationship between depression, anxiety, and stress among Saudi lawyers concerning whether case specialization, gender, or years of experience are significant in affecting psychological distress. In a survey of 79 lawyers, male lawyers held higher levels of distress than female lawyers, and criminal lawyers were more distressed than those in commercial or general law. In addition, experienced lawyers were more depressed and stressed than inexperienced ones. These findings lay the importance of developing interventions on mental health in Saudi legal professionals to decrease psychological distress and improve their positive psychological health.